Seismic Performance Evaluation of Friction Damper and Yielding Metallic Damper in Steel Frame (Journal of Civil Engineering Researchers, 2023)
In recent decades, various control systems have been studied to reduce the vibrations of structures under dynamic forces. Generally, types of structural control systems are classified into energy dissipation systems and seismic isolation systems. Examples of energy dissipation systems include metallic yielding dampers, friction dampers, viscoelastic dampers, viscous dampers, tunable mass dampers, and tunable liquid dampers. This article investigates the seismic performance of friction dampers and metallic yielding dampers in steel frames, as well as the performance of a two-story steel frame strengthened with metallic yielding dampers and combined with friction dampers. For this purpose, five two-story steel frames with eight-story divergent braces were examined: a frame without a damper, a two-story frame with metallic yielding dampers, a two-story frame with friction dampers, a two-story frame with the first floor having friction dampers and the second floor having metallic yielding dampers, and a two-story frame with the first floor having metallic yielding dampers and the second floor having friction dampers. The results show that the use of dampers increases the energy dissipation of the structure and reduces the maximum displacements induced in the structure as well as the base shear. The effect of metallic yielding dampers on reducing the base shear is greater than that of friction dampers, while the effect of friction dampers on increasing energy dissipation and reducing displacements induced in the structure is greater compared to metallic yielding dampers
Keywords: Yielding metallic damper; Friction damper; Energy dissipation; Displacement; Base shear